2007
DOI: 10.1029/2006jc003580
|View full text |Cite
|
Sign up to set email alerts
|

Geological controls and tidal forcing of submarine groundwater discharge from a confined aquifer in a coastal sand dune system

Abstract: [1] Submarine groundwater discharge (SGD) into the ocean is increasingly recognized as an important component of land-ocean interaction. Numerous geological settings may be the source of terrestrially derived SGD, including spatially extensive sand dune systems, which are a common coastal setting in tropical, subtropical, and temperate regions throughout the world. Within the catchment of the Great Barrier Reef lagoon, numerous large-scale sand dune systems exist. Creeks and rivers draining these systems are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
2
8
0
2
Order By: Relevance
“…They found that the discharge was inversely related to the tide: low tide produced the strongest discharge, and at high tide, the discharge weakened and could even reverse. Similar results were reported for a submarine spring in Australia [24]. Parra et al [26,27] also report similar results for springs in the Mexican Caribbean coast.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…They found that the discharge was inversely related to the tide: low tide produced the strongest discharge, and at high tide, the discharge weakened and could even reverse. Similar results were reported for a submarine spring in Australia [24]. Parra et al [26,27] also report similar results for springs in the Mexican Caribbean coast.…”
Section: Introductionsupporting
confidence: 79%
“…Holliday et al [24] analyze the geologic controls on submarine groundwater discharge from a confined aquifer and Fleury et al [25] present a review of submarine springs located in karstic aquifers. They found that the main mechanisms involved in the hydrodynamics of the submarine springs are the aquifer discharge and the saline intrusion through conduits.…”
Section: Introductionmentioning
confidence: 99%
“…7) were used to estimate the water volume change over time ( . This seasonal variability in karstic groundwater inputs is likely linked to variations on the terrestrial hydraulic gradient, as commonly observed in groundwater studies in coastal systems (Garcia-Solsona et al, 2010;Holliday et al, 2007;Rodellas et al, 2012;Smith et al, 2008).…”
Section: Water Mass Balancementioning
confidence: 72%
“…Naturally, the coastal aquifers are in equilibrium with respect to the freshwater-saline water interface 2186 Hydrological Sciences Journal -Journal des Sciences Hydrologiques, 59 (12) 2014 http://dx.doi.org/10. 1080/02626667.2013.871013 and flow to the sea with minor oscillations affected by tidal heights (Holliday et al 2007). Generally, coastal freshwater zones have limited potential (volume wise) and such strategic resources are always precarious when they are over-exploited.…”
Section: Introductionmentioning
confidence: 99%